EFEKTIVITAS MODEL RECIPROCAL TEACHING TERHADAP HASIL BELAJAR SISWA MAN 2 PONTIANAK - Febriyanto, Febriyanto; Herkulana, Herkulana; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to investigate the effectiveness of reciprocal teaching model in learning to the result of the students in learning international cooperation at social XI MAN 2 Pontianak. The method of this research was quasi experimental research with Nonequivalent Control Group Design. The sample of this research was the students of social in second grade, and the control group of this research was the students of social in first grade. The result of this research found that the mean score of the students in learning international cooperation was 77,69 and the mean score of control group was 75,00. The difference between post-test in two group get the t-count 2,14 and t-table with significant level 5% or 0,05 so it were tested in two sides t count > t-table (2,14>1,99), it can be seen in sig. The level of significant (Sig. 2-tailed) with 0,035 it means the level of significant < 0,05 (0,035 < 0,05). Referring to the research findings, there was a difference between the result of post-test with the experiment and control group. It can be concluded that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Based on the effect size obtained 0,49 in the result of learning achievement. Keyword : Reciprocal Teaching, Learning Achievement, International Cooperation